2023
DOI: 10.3389/fpsyt.2023.1145783
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in prepulse inhibition of the startle response

Abstract: IntroductionAcoustic prepulse inhibition of the startle response (PPI) is a phenomenon characterized by the reduction in the startle reflex caused by the presence of weak and brief stimulus before an intense and sudden stimulus (pulse). These phenomena can be observed in several species, but in humans it is commonly measured by the eyeblink using electromyography. PPI works as an operational measure of sensorimotor gating, which is the ability to suppress motor responses for sensory stimulus. Healthy aging is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The PPI of the acoustic startle reflex and the current PPI have similar age and sex biases, but different age and sex effects on the test response: the elderly showed a weaker acoustic startle reflex in previous studies (Ellwanger et al, 2003;de Oliveira et al, 2023), but not in the present study (Figure 3C), and females showed stronger test alone responses in this study, but not for the acoustic startle reflex (Kumari et al, 2004). The most important methodological difference may be that the acoustic startle reflex was the peripheral response in previous studies and the brain response in the present study.…”
Section: Methodological Considerationmentioning
confidence: 58%
See 2 more Smart Citations
“…The PPI of the acoustic startle reflex and the current PPI have similar age and sex biases, but different age and sex effects on the test response: the elderly showed a weaker acoustic startle reflex in previous studies (Ellwanger et al, 2003;de Oliveira et al, 2023), but not in the present study (Figure 3C), and females showed stronger test alone responses in this study, but not for the acoustic startle reflex (Kumari et al, 2004). The most important methodological difference may be that the acoustic startle reflex was the peripheral response in previous studies and the brain response in the present study.…”
Section: Methodological Considerationmentioning
confidence: 58%
“…A recent study using the trigeminal blink reflex showed that PPI of the early component of the blink reflex occurred in the first stage of brain processing in the principal nucleus of the trigeminal nerve and did not involve higher complex processes ( Inui et al, 2023 ). In studies with PPI of the acoustic startle reflex, one reported decreased inhibition in older subjects ( de Oliveira et al, 2023 ), while others reported no effect of age ( Filion and Poje, 2003 ; Scholes and Martin-Iverson, 2009 ) or an inverted U-shaped relationship between age and PPI, with the strongest inhibition in middle age ( Ellwanger et al, 2003 ). PPI of the trigeminal blink reflex by somatosensory inputs showed no age effect ( Kofler et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation